Loan recovery management in primary co-operative agricultural and rural development banks in Kerala - Renjitha N T (Department of Rural Banking and Finance Management, College of Co-operation Banking and Management, 2004)
The study entitled "Loan Recovery Management in Primary Co-operative Agricultural and Rural Development Banks in Kerala" was conducted to examine the effectiveness of the existing loan recovery management of Primary Co-operative Agricultural and Rural Development Banks in Kerala and to identify the factors influencing recovery. The study was conducted among four PCARDBs of Ernakulam and Thrissur district viz., Kanayannur CARDB (B 1), Ernakulam CARDB (B2), Cochin CARDB (B3) and Irinjalakuda CARDB (B4). The sample size included 80 respondents i.e., 20 borrowers from each bank at random, of which 15 were defaulters and five were non-defaulters or prompt repayers. Ten officials (including secretaries and BODs) from each bank were also interviewed to collect information on the effectiveness of the loan recovery system of the banks. Secondary data on selected performance indicators of the banks were also used for the study. Statistical tools like AAGR, simple averages, percentages, simple growth rate, simple correlation, efficiency index, priority index and bi-variate tables were used for the analysis. The analysis on the overdue amount of the selected PCARDBs, revealed that Cochin CARDB (B3) had the highest amount of overdues among all the banks, , during the reference period. Profits of all banks have eroded due to provisronmg for accumulated overdues. B4 has shown the best performance in terms of lower overdues and higher profitswhen compared to the other banks. An increase in the demand for nOI1- agricultural loans, particularly RHLs was found, which indicates a shift in the lending pattern. Overdues above four years were growing tremendously in all the banks. Most of the females were found to be prompt repayers. Inspite of having better education, the borrowers were creating huge overdues. This indicates the existence of wilful defaulters. The study found that the defaulters of all t11:;: banks except B4, having annual income above the subsistence level had higher am aunt of